STRATEGI GURU BK DALAM PEMILIHAN PENJURUSAN KARIR SISWA KELAS X DI SMA NEGRI 1 BANDA ACEH - Anggia Fadila; Muslima; Usfur Ridha (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Career major selection is an important decision for senior high school students because it influences their educational pathway and future career planning. However, many students experience difficulties in choosing a major that matches their interests, abilities, and career aspirations, highlighting the role of Guidance and Counseling teachers. This study aimed to describe the strategies employed by Guidance and Counseling teachers in assisting tenth-grade students at SMA Negeri 1 Banda Aceh in selecting career majors and to identify the factors influencing this process. This study employed a qualitative descriptive approach. The participants consisted of one Guidance and Counseling teacher and three tenth-grade students. Data were collected through in-depth interviews, preliminary observations, and documentation and were analyzed using the Miles, Huberman, and Saldaña model. The findings revealed that Guidance and Counseling teachers implemented career information services, individual counseling, interest and aptitude identification, and collaboration with teachers and parents. Career major selection was influenced by internal and external factors. These strategies improved students' career readiness and the accuracy of their career major selection.